PP.25.01: CLONIDINE. (June 2015) - Ribeiro, H.; Pereira, S.; Dias, V. Paixão; Fernandes, J.C.
Abstract : Objective: To evaluate the characteristics of patients receiving clonidine and its effect on Blood Pressure (BP). Design and method: Retrospective study of patients with chronic kidney disease (CKD) evaluated in Clinic Consultation of Nephrology / Nephrology Hypertension, with uncontrolled hypertension who were treated with clonidine. Glomerular filtration rate (GFR) was estimated according to MDRD formula. BP was considered controlled if <140/85 mmHg or < = 130 /80 mmHg in diabetics or in patients with proteinuria. Results: In 232 patients, 21 (9.1%) of the hypertensive patients were treated with clonidine. The median age was 72 years and 61.9% (13) were female. Parenchymal secondary cause for hypertension was present in 76.2% of patients, followed by renovascular etiology (19.1%) and hyperaldosteronism (4.8%). Other vascular risk factors present were dyslipidemia (90.5%) and diabetes mellitus (81%). Cerebrovascular disease was present in 19% of the patients. Regarding the CKD, 57.1% had GFR of stage 4 (15–30 mL/min) and 5 (<15 mL/min) due, most often, to isquemic nephropathy and hypertensive nephroangiosclerosis. When clonidine was introduced, 20 patients were taking at least three different classes of drugs (average of 4 antihypertensive/patient). After its introduction (66.7% treated with median dose of 0, 075 mg 2id), hypertension was controlled in 52.4% of patients, but 3 patients reported xerostomy while only 1 patient withdrew the drug due to hypotension. These are preliminary results. Conclusions: In patients with chronic kidney disease hypertension is prevalent and often is very difficult to control, not only due to the severity of the disease itself but also due to the necessary personalization of prescribed drugs. Central acting alpha agonists are useful as "adjuvant" therapeutic drugs increasing the proportion of patients with controlled disease.